Greening healthcare and slashing carbon emissions through telemedicine: a cross-sectional study from over 50 thousand remote consults at a leading tertiary hospital - Roberto Nunes Umpierre; Roberto Nunes Umpierre; Roberto Nunes Umpierre; Roberto Nunes Umpierre; Rita Mattiello; Rita Mattiello; Rita Mattiello; Carlos André Aita Schmitz; Carlos André Aita Schmitz; Carlos André Aita Schmitz; Enrique Falceto de Barros; Enrique Falceto de Barros; et al. (Frontiers in Digital Health)
IntroductionMinimizing healthcare systems’ resource footprints is crucial. To expand this focus, our objective was to assess the carbon emission reductions achievable through the introduction of telemedicine services at a prominent Brazilian tertiary hospital.MethodsThis cross-section study included all patients who had remotely held appointments in a Brazilian tertiary hospital. The primary outcome was carbon emissions. The estimated carbon emissions were first calculated based on the distance between the hospital and the patient's home address. After, the calculated distance was multiplied by the amount of carbon estimated according to the type of transport used.ResultsThe study included 28,244 patients undergoing 52,878 remote appointments between March and December 2020, residing in 417 municipalities in Rio Grande do Sul and 80 towns in other Brazilian states. The total sum of distances and carbon gas reduction saved with the implementation of remote consultations amounted to 805,252.00 km and 939,641.94 kg of CO2 emissions, respectively.DiscussionTelemedicine initiatives implemented in tertiary hospitals for less than a year result in a large amount of greenhouse gas emissions saved. Telemedicine emerges as a promising strategy with significant potential to mitigate the impact on planetary health.